A mysterious something in the light : the life of Raymond Chandler - Williams, Tom, 1981- (Chicago Review Press, 2013)
"The life of Raymond Chandler has long been obscured by secrets and half-truths as deceptive as anything in his novel The Long Goodbye. Now, drawing on new interviews, previously unpublished letters, and archives on both sides of the Atlantic, Tom Williams casts a new light on this most mysterious of writers. Raymond is a man troubled by loneliness and desertion from an early age. Born in Chicago in 1888, his childhood was overshadowed by the collapse of his parents' marriage, his father's alcohol-fuelled violence eventually forcing the boy and his doting mother to leave for Ireland and later London. but class-bound England proved stifling, and Chandler, in his twenties and eager to forge a new life, returned to the US where--in corruption-ridden LA--he met his one great love, Cissy Pascal, a married woman eighteen years his senior. It was only during middle age, later his alcoholism wrecked a lucrative career an oilman, that Chandler seriously turned to crime fiction. And Philip Marlowe endures."--From publisher's description.